Front Cover: Flexible Fragment Growing Boosts Potency of Quorum‐Sensing Inhibitors against Pseudomonas aeruginosa Virulence (ChemMedChem 2/2020). (24th January 2020) - Zender, Michael; Witzgall, Florian; Kiefer, Alexander; Kirsch, Benjamin; Maurer, Christine K.; Kany, Andreas M.; Xu, Ningna; Schmelz, Stefan; Börger, Carsten; Blankenfeldt, Wulf; Empting, Martin
Abstract : The Front Cover illustrates key steps of a successful fragment‐growing campaign starting from an enthalpy‐driven, high‐affinity fragment identified via biophysical methods against bacterial quorum sensing receptor PqsR. This transcription regulator is an attractive drug target for the design of so‐called pathoblockers against Pseudomonas aeruginosa infections. Allowing flexibility in the compound enlargement process facilitated probing deeper into the binding pocket accompanied by a strong boost in potency. The resulting optimized hit showed promising antivirulence characteristics qualifying it as a suitable starting point for further optimization into lead compounds. More information can be found in the Full Paper by Michael Zender, Martin Empting et al. on page 188 in Issue 2, 2020 (DOI: 10.1002/cmdc.201900621 ).